2018
DOI: 10.1038/s41467-018-05815-z
|View full text |Cite
|
Sign up to set email alerts
|

Systematic mapping of BCL-2 gene dependencies in cancer reveals molecular determinants of BH3 mimetic sensitivity

Abstract: While inhibitors of BCL-2 family proteins (BH3 mimetics) have shown promise as anti-cancer agents, the various dependencies or co-dependencies of diverse cancers on BCL-2 genes remain poorly understood. Here we develop a drug screening approach to define the sensitivity of cancer cells from ten tissue types to all possible combinations of selective BCL-2, BCL-XL, and MCL-1 inhibitors and discover that most cell lines depend on at least one combination for survival. We demonstrate that expression levels of BCL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 39 publications
11
95
0
Order By: Relevance
“…NOXA induction may ensue from a complex interaction between NF-κB and type I Interferon signaling as we incriminated IRF3, which was established as a key regulator of IFNα/β receptor-mediated feedforward regulation and crosstalk with other pathways 22,36 and detected a slight recruitment of RelA. As cancer cells frequently rely on the complementary activities of BCL-xL and MCL-1 for their survival 15,37,38 we propose that the paracrine effects of paclitaxel, through IFN/TNF dependent NOXA induction, enhance BCL-xL dependency by decreasing the influence of MCL-1. This implies that the paracrine effects of paclitaxel will be overtly letal provided BCL-xL expression in cancer cells is relatively low, a feature that was associated with sensitivity to chemotherapy in triple negative breast cancers (TNBC) 37 .…”
Section: Discussionmentioning
confidence: 93%
“…NOXA induction may ensue from a complex interaction between NF-κB and type I Interferon signaling as we incriminated IRF3, which was established as a key regulator of IFNα/β receptor-mediated feedforward regulation and crosstalk with other pathways 22,36 and detected a slight recruitment of RelA. As cancer cells frequently rely on the complementary activities of BCL-xL and MCL-1 for their survival 15,37,38 we propose that the paracrine effects of paclitaxel, through IFN/TNF dependent NOXA induction, enhance BCL-xL dependency by decreasing the influence of MCL-1. This implies that the paracrine effects of paclitaxel will be overtly letal provided BCL-xL expression in cancer cells is relatively low, a feature that was associated with sensitivity to chemotherapy in triple negative breast cancers (TNBC) 37 .…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, we determined the expression of apoptosis‐related markers by Western blotting (Figure A). Anti‐apoptotic (Bcl‐2) and pro‐apoptotic (cleaved caspase‐3) proteins play crucial roles in controlling cells apoptosis . Significant increases in cleaved caspase‐3 and decreased Bcl‐2 expression were observed in Bcap‐37 cells transfected with PLAC8 siRNA, whereas T47D cells overexpressing PLAC8 exhibited the opposite effect.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-apoptotic (Bcl-2) and pro-apoptotic (cleaved caspase-3) proteins play crucial roles in controlling cells apoptosis. [23][24][25][26] Significant increases in cleaved caspase-3 and decreased Bcl-2 expression were observed in Bcap-37 cells transfected with PLAC8 siRNA, whereas T47D cells overexpressing PLAC8 exhibited the opposite effect. Furthermore, the cell cycle analysis results indicated that more Bcap-37 cells transfected with si-PLAC8 were in the G0/1 phase than that observed for the control cells ( Figure 5B), and these results were consistent with those observed in T47D cells.…”
Section: Plac8 Silencing Induces Caspase 3/9 Activation Bcl-2 Up-rmentioning
confidence: 98%
“…The absence of efficacy achieved with ABT-737 and BRAFi in the context of resistance may be driven by a unique repertoire of BCL2 proteins in melanocytes (45, 46, 49-51, 54, 56). In addition, proapoptotic BH3-only proteins' expression patterns or their different binding affinity to the antiapoptotic proteins can induce different dependencies on BCL2 proteins (34,45,57). Recently, Lee and colleagues defined that BCL-XL and MCL1 dual targeting is critical to blunt melanoma cell survival, but it remains to be determined whether their combination targeting would reduce MAPKi-resistant melanoma cell viability (58).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, successful clinical trials of venetoclax (ABT-199), a specific BCL2i, has led to its FDA approval for chronic lymphocytic leukemia and clinical evaluation for treatment of other cancers (41)(42)(43)(44). However, single-agent inhibition of BCL2 is not sufficient to induce cell death of melanomas due in part to differential BCL2 protein expression and diversity (45)(46)(47)(48)(49)(50)(51). Similarly, ABT-199 failed to significantly reduce BRAF-mutant melanoma cell viability alone or in combination with TTM in the high-throughput screen ( Supplementary Fig.…”
Section: Bh3 Mimetics Synergize With Ttm To Reduce Cell Viability Of mentioning
confidence: 99%